Phagocytosis of Giardia muris by macrophages in Peyer's patch epithelium in mice - Robert L. Owen; C. Allen; David Stevens (1981)
No mechanism for the initiation of immunological clearance of Giardia from the mammalian intestinal tract has been identified. In normal and nude mice experimentally infected with G. muris, we examined antigen-sampling epithelium over Peyer's patch follicles by electron microscopy for evidence of interaction between G. muris and lymphoid cells. Invading G. muris were found in the epithelium near dying or desquamating columnar cells. Macrophages beneath the basal lamina extended pseudopods into the epithelium, trapping invading G. muris and enclosing them in phagolysosomes. In normal mice, which clear G. muris in 4 to 6 weeks, macrophages containing digested G. muris were surrounded by rosettes of lymphoblasts in the epithelium. In nude mice deficient in lymphocytes, there was apparent hyperplasia of macrophages, which filled the follicle domes, resulting in more frequent entrapment of G. muris but no contact between macrophages and lymphoblasts in the epithelium. In nude mice, which require 6 months to control G. muris infection, lymphoblast contact with macrophages containing distinctive microtubular remnants of G. muris was only identified in the follicle dome. This close physical association of lymphoblasts and macrophages containing G. muris remnants suggests that this macrophage activity represents intraepithelial antigen processing as well as a defense against the effects of the uncontrolled entrance of microorganisms and other antigenic particles into Peyer's patch lymphoid follicles.